Effect of multi-arc ion plating process on coating performance of cemented carbide PCB milling cutter - Xiaofan YANG; Haiyang LIN; Yicong CHEN; Rongjie JI; Zhihuang SHEN; Lingxiang LI (Jin'gangshi yu moliao moju gongcheng, 2023)
The preparation of a high-performance hard coating on the surface of a carbide PCB (Printed Circuit Board) milling cutter can address the issue of rapid tool wear during cutting. In this study, AlCrN single coating, CrN/AlCrN composite coating and AlCrSiN/AlCrN composite coating were prepared on YG06 cemented carbide specimens and PCB milling cutter substrates by a multi-arc ion plating process, respectively. The mechanical properties and morphological characteristics of the three coatings were observed and analyzed using an indenter and a scanning electron microscope. The above three coated milling cutters were tested under the same conditions, and the coating performance and the tool wear mechanism were compared and analyzed. The results show that the coatings prepared by the above three processes exhibit good film-base adhesion, with the AlCrSiN/AlCrN composite coating milling cutter having the longest service life — approximately 1.5 times that of the CrN/AlCrN coating milling cutter and 1.9 times that of the AlCrN single coating milling cutter. The AlCrSiN/AlCrN composite coating demonstrates the best compactness and surface quality, making it more suitable for high-speed machining of PCB (IT158 copper-clad laminate).